PEMODELAN EKONOMETRIKA AGRESIVITAS PEMBERIAN KREDIT DI BANK PERKREDITAN RAKYAT - Agus Ardiana, Putu; Indah Purnama Sari, Ni Putu (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 6 No 1 (2011), 2011)
This paper aims to investigate independent variables affecting loanaggressiveness of rural banks proxied by the growth of loan through aneconometric modeling. We initially identified 13 variables affecting the ratio butwe then dropped a number of independent variables insignificantly affecting thedependent variabel. Conducting 13 modelling, the last econometric model is aBLUE (Best Linear Unbiased Estimators) model implying that the model has noclassical assumptions problems at all. The BLUE model suggests thatindependent variables affecting loan aggressiveness of rural banks are thegrowth of third-party deposits and Return on Assets (ROA).
Keywords: Rural Banks, Loan Aggressiveness, Growth of Third-Party Deposit and ROA